Temporal Dynamics in Density of the Freshwater Mussel, Lamellidens marginalis, in a Lentic Habitat of Bangladesh - Fariha, Fouzia; Billah, Tashrif; Rana, Md Masud; Chandro, Bishjiet; Uddin, Md Jasim (Journal of the Bangladesh Agricultural University, 2025)
Freshwater mussel, Lamellidens marginalis (Lamarc, 1819), is a commercially important species in Bangladesh. It is widely used in pearl, lime, and poultry food production. Information about temporal variation of L. marginalis population in aquatic ecosystems is inadequate in Bangladesh. Hence, it is difficult to plan farming and harvesting of L. marginalis. A year-long study was conducted at a culture pond in Mymensingh, Bangladesh to understand the temporal variation of L. marginalis population during April 2023–March 2024. Quadrat method was used to estimate its natural population in the pond of 502 m2 area. Mussels were collected monthly by hand-picking from eight distant quadrats across the pond, each having an area of 4 m2. Their mean population in the pond varied from 988 to 2071 individuals where minimum being in September and maximum being in April. The pond’s water quality parameters–depth, temperature, and pH–were simultaneously monitored to correlate with mussel population. The annual mean depth, temperature, and pH were 1.51 m, 23.59 °C, and 7.37, respectively. Depth was found to be significantly negatively correlated (Spearman’s= -0.97, P < 0.001) with population size. No substantial correlation was found between population and temperature or population and pH. Biometric characteristics of the mussels were also recorded during the study. The mean shell length, width, and height were 92.10, 44.05, and 20.27 mm, respectively. Overall, this study provides a basis for farming and harvesting quality mussels in a lentic habitat. The collected data have been released publicly via GitHub to facilitate future mussel population dynamics research. J Bangladesh Agril Univ 23(4): 548–558, 2025